PEMANFAATAN PUPUK ORGANIK CAIR PAITAN (Tithonia diversifolia) PADA BERBAGAI DOSIS DAN RAGAM APLIKASINYA TERHADAP PERTUMBUHAN KAILAN (Brassica oleracea Var. Acephala) - AHMAD TAOFIK; SOFIYA HASANI; AYU CAHYANINGTYAS; BUDY FRASETYA (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The paitan plant contains allelopathic compounds for other plants so that the utilize of paitan plant as a source of liquid organic fertilizer (LOF) has not been widely applied. This research aimed to study the interaction between LOF dosage and appropriate application method of LOF to increase the growth of kailan plants. The research conducted at experimental garden of UIN Bandung from June-August 2016. The experimental design was a completely randomized design with two factors and replicated four times. The first factor was application methods (A), i.e. a1=direct application to the soil, and a2= spraying. The second factor was LOF dosage (T), i.e. t0: 0 ml plant-1, t1: 20 ml plant-1, t2: 40 ml plant-1, t3: 60 ml plant-1, t4: 80 ml plant-1. The growth parameters observed i.e. plant height (14, 21, 28, 35 and 42 Day after Transplanting (DAT)), leaf area 42 DAT, plant dry weight 42 DAT, and plant fresh weight 42 DAT. The data then analyzed with analysis of variance at a significant level of 5%. If the analysis of variance was significant, the Duncan multiple range test was used at α=5%. The research results showed there was no interaction between method of application with a various dosage of paitan LOF to all of the growth parameters. The application paitan LOF showed similar growth in terms of plant height, leaf area, plant dry, and plant fresh weight. The application method of paitan LOF direct to the soil or spraying to leaves can not increase kailan plant growth.